Mental Health of Social Media Users In Indonesia By Gender - Wahyudi Rahmat; Ricci Gemarni Tatalia; Gita Wincana; Afdalil Aflika Putra (Bakaba, 2022)
In this era of advanced technology, individuals no longer interact with others directly; they can also interact with others indirectly, particularly through the availability of technology that facilitates social media. Technological progress has always been pitted against modernity, which is equal to progress in human life. When utilizing social media, one doesn't have to worry about being judged for the comments and opinions they share with other users. However, when people use social media, they often do it to evoke positive emotions; however, they may not realize that the use of social media may have the opposite effect and lead to negative outcomes for them. Besides being able to have a significant influence on user actions, the use of social media can also cause users mental health problems